LIMITS ON THE MASS FLUX BETWEEN LOWER AND UPPER MANTLE AND STABILITY OF LAYERING - O'Nions R.K.; Tolstikhin I.N. (My University, 1996)
Geochemical arguments for a layered mantle based upon both lithophile and rare gas element abundances are well established. The negative Clayperon slope, associated with phase changes at 670 km, is expected to impede circulation between the upper and lower mantle and induce layering at this depth.Consideration of estimates for the He and Ar isotopic composition of the upper and lower mantle, together with 36Ar and 40Ar abundances in the atmosphere, place limits on the mass flux between the lower and upper mantle when combined with estimates for K, U and Th. Using the assumption that rare gases have steady-state abundances in the upper mantle (with residence time τ = 1 Ga), then the time-averaged mass flux from the lower mantle is ≤2 · 1013 kg a−1. The estimated mass flux is at least 50 times less than the present-day slab flux of ∼ 1015 kg a−1.The result imposes restriction on the amount of upper mantle material and the frequency with which possible avalanches into the lower mantle might occur and further suggests that models of episodic crustal growth related to such effect are unlikely to be correct.